Mangrove distribution in Tioman and Tulai Island, Pahang, Malaysia - Saad, Shahbudin; Ahmad, Zuhairi; Rani, Husaini; Khodzori, Mohd Fikri Akmal; Yusof, Muhammad Hamizan (2013)
Tioman Island is not only popular with numerous corals reef and fishes species but also its inland rainforest area such as mangroves. Mangroves composition and species was richly diverse in Tioman and Tulai Island. A total of 23 mangrove species has been found consist of exclusive and non• exclusive species; an indication of high mangrove diversity and species richness in Kg. Juara, Kg. Nipah, Kg. Paya, Kg. Genting and Tulai Island. The abundance mangrove species are Rhizophora X lamarckii, Rhizophora apiculata, Rhizophora mucronata and Brugueira gymnorrhiza. Images from Landsat-7 ETM+ of Tioman and Tulai lsland were analyzed using supervised classification and Principal Component Analysis (PCA). Results indicated that total of 59.895 hectares mangrove covers have been identified in both islands, with 86.49% in Tioman Island (52.7625 hectares) and 13.51% in• Tulai Island (7.1325 hectares). Remote sensing and GIS application found to be useful as the technology allowed monitoring and mapping large scale area of mangrove forest.